Dual and Multiple Diagnosis Among Substance Using Runaway Youth - Slesnick, Natasha (2005)
Although research on runaway and homeless youth is increasing, relatively little is known about the diagnostic profile of runaway adolescents. The current study examined patterns of psychiatric dual and multiple diagnosis among a sample (N = 226) of treatment-engaged substance-abusing youth (ages 13 to 17) who were residing at a runaway shelter. As part of a larger treatment outcome study, the youths’ psychiatric status was assessed using the DSM-IV based computerized diagnostic interview schedule for children [CDISC; (1)]. The majority of the youth in our sample met criteria for dual or multiple diagnosis (60%) with many having more than one substance-use diagnosis (56%). The severity of mental-health and substance-use problems in this sample of substance-abusing runaways suggests the need for continued development of comprehensive services. The range and intensity of diagnoses seen indicates a need for greater focus on treatment development and strategies to address their multiple areas of risk.